1998
DOI: 10.1111/j.1600-0749.1998.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Kinetics: Failure of Acceleration in Oxidation of Ring‐Blocked Monohydric Phenol Substrate

Abstract: When 2,5,6-trimethyl-4-hydroxyanisole is used as substrate for mushroom tyrosinase the oxidation rate is slow and the kinetics do not exhibit an initial acceleration (lag period), in contrast to the kinetics of oxidation of the parent compound, 4-hydroxyanisole. This finding is interpreted as evidence that the acceleration of oxidation of 4-hydroxyanisole is indirectly contingent on a reductive nucleophile addition to the orthoquinone product of the monohydric phenol, which is prevented by ring methylation. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…9,10) The melanocytes produce melanin by a process that involves the transformation of tyrosine into 3,4-dihydroxyphenylalanine (DOPA) by the enzyme tyrosinase and the subsequent transformation of DOPA into melanin. 5,11,12) Tyrosinase is the key enzyme in the pathway of melanogenesis. Tyrosinase plays a regulatory role in the production of melanin.…”
mentioning
confidence: 99%
“…9,10) The melanocytes produce melanin by a process that involves the transformation of tyrosine into 3,4-dihydroxyphenylalanine (DOPA) by the enzyme tyrosinase and the subsequent transformation of DOPA into melanin. 5,11,12) Tyrosinase is the key enzyme in the pathway of melanogenesis. Tyrosinase plays a regulatory role in the production of melanin.…”
mentioning
confidence: 99%
“…The cells were detached from culture bottles using 0.025% trypsin and 0.5 mM ethylenediaminetetra acetic acid in phosphate-buffered saline (PBS). B16F0 melanoma cells were seeded into 6-well plates at a density of 1ϫ10 5 Amino acids, the building blocks of proteins, play significant roles in numerous physiological events in mammals. As the effects of amino acids on melanogenesis have yet to be demonstrated, the present study was conducted to identify whether amino acids, in particular alanine, glycine, isoleucine and leucine, influence melanogenesis in B16F0 dose of sample reagent was added to a well and incubated for another 72 h. After each incubation, cells were washed with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…2,3) Melanin is synthesized in the melanosomes of melanoma cells, which produce melanin by a process that involves the transformation of tyrosine into 3,4-dihydroxyphenylalanine (L-DOPA) by the enzyme tyrosinase and the subsequent transformation of L-DOPA into melanin. 4,5) Tyrosinase is the key enzyme in the pathway of melanogenesis, and plays a regulatory role in the production of melanin. [6][7][8] Accordingly, the regulation of tyrosinase may not only control melanin production but also provide a strategy for hypopigmentation.…”
mentioning
confidence: 99%
“…It was reported that the presence of at least small amount of oxytyrosinase in the native enzyme is essential to produce sufficient amount of diphenol and establish the active monophenolase cycle [41]. The met-tyrosinase form lacks monophenolase activity since binding of monophenol to this form scavenges part of tyrosinase from the catalytic turnover as a dead-end complex in the steady state of monophenolase activity [41][42][43][44]. The change of the pH stability for oxy-tyrosinase in different mushroom PPOs may be related with differences in the environmental conditions during development of mushrooms and/or differences in maturity stage of mushrooms that may be Fig.…”
Section: Ph Stabilitymentioning
confidence: 99%